IMPLEMENTATION OF NORMATIVE ECONOMY ON BUSINESS ACTIVITY IN THE PERIOD OF RASULULLAH SAW - Telsy Fratama Dewi Samad; Rosdalina Bukido (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2021)
Nowadays not all entrepreneurs implement the concept of normative economy in conducting their business activity, particularly Muslim entrepreneurs which it relates to Islamic Economic Principle. The purpose of this article is to analyze the implementation of normative economy on business activity in the period of Rasulullah SAW. This article uses qualitative methods with the analysis of literacy study approach. The result of this paper shows that Prophet Muhammad SAW has carried out business activities based on normative economic concepts that emphasize ethics in conducting business. As the Prophet said; I have been sent to perfect the moral standard, narrated by Abu Hurairah. The conclusion of this article is that ethics is a principal aspect in business since according to Islam those economic activities cannot be separated from ethics. Thus, it is essential for Muslim entrepreneur to implement ethics on their business activity.